Active MS is associated with accelerated retinal ganglion cell/inner plexiform layer thinning - Ratchford, John N. (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: To determine the effect of clinical and radiologic disease activity on the rate of thinning of the ganglion cell/inner plexiform (GCIP) layer and the retinal nerve fiber layer in patients with multiple sclerosis (MS) using optical coherence tomography (OCT). METHODS: One hundred sixty-four patients with MS and 59 healthy controls underwent spectral-domain OCT scans every 6 months for a mean follow-up period of 21.1 months. Baseline and annual contrast-enhanced brain MRIs were performed. Patients who developed optic neuritis during follow-up were excluded from analysis. RESULTS: Patients with the following features of disease activity during follow-up had faster rates of annualized GCIP thinning: relapses (42% faster, p = 0.007), new gadolinium-enhancing lesions (54% faster, p < 0.001), and new T2 lesions (36% faster, p = 0.02). Annual GCIP thinning was 37% faster in those with disability progression during follow-up, and 43% faster in those with disease duration <5 years vs >5 years (p = 0.003). Annual rates of GCIP thinning were highest in patients exhibiting combinations of new gadolinium-enhancing lesions, new T2 lesions, and disease duration <5 years (70% faster in patients with vs without all 3 characteristics, p < 0.001). CONCLUSIONS: MS patients with clinical and/or radiologic nonocular disease activity, particularly early in the disease course, exhibit accelerated GCIP thinning. Our findings suggest that retinal changes in MS reflect global CNS processes, and that OCT-derived GCIP thickness measures may have utility as an outcome measure for assessing neuroprotective agents, particularly in early, active MS.